Autoimmune Hemolytic Anemia. Review of 43 Cases - Lopez-Vidal, H (SOC MEDICA SANTIAGO, 2019)
Background: Autoimmune hemolytic anemia (AIHA) is an uncommon disease. In its presentation, it can be severe and even lethal. There is only one clinical report concerning this pathology in Chile. Objective: To describe the clinical characteristics and evolution of adult AIHA inpatients. Materials and Methods: Retrospective review of clinical records of adult AIHA inpatients between January 2010 and June 2018 was done. Demographic, clinical, laboratory and therapeutic information was analyzed. A descriptive, analytical and survival analysis was performed. Results: Forty-three adult patients diagnosed with AHIA were hospitalized in a period of 8 years. Median age was 63 years (range 22-86 years), mostly women (72%). Warm antibodies were detected in 36 cases (84%) and cold antibodies in seven. Seventy two percent of the patients had an underlying cause, and 58% were secondary to lymphoproliferative neoplasms. All patients except two, received steroids as initial treatment, with response in 37 (90%) of them. Three refractory patients received rituximab, with response in all of them, and relapse in one. Median follow-up was 38 months (range 2-98 months). Five year overall survival was 72%. Conclusion: AHIA in adults inpatients is a heterogeneous disease, mainly due to warm antibodies, and to secondary etiology.